2017
DOI: 10.1016/j.ijscr.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Mesh erosion to urinary bladder causing fistulation to abdominal wall resulting in necrotizing fasciitis: A case report of late complication of incisional hernia

Abstract: HighlightsIncisional hernia is not an uncommon complication after abdominal operation.Mesh migration and erosion causing vesico-cutaneous fistula and subsequent necrotizing fasciitis is uncommon.We hereby report a case of abdominal wall necrotizing fasciitis 21 months after laparoscopic incisional hernia repair in lower midline with dual mesh, due to mesh migration and erosion into urinary bladder, resulting in fistulation between bladder and abdominal wall.Mesh erosion to viscera can cause severe complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…612 The presence of poly n-butylcyanoacrylate as a major component of urine bladder stone in our patient leads to an assumption that poly n-butylcyanoacrylate used in therapy of seroma was released into the bladder and thus became the crucial part of the concretion formation. The mechanism of the cyanoacrylate release into the bladder could be also explained by the mesh erosion caused by secondary migration as a result of erosion of the surrounding tissue, 1315 but this was not the case of our patient. Some recent studies demonstrated cyanoacrylate bladder stone formation following occlusion of vesicosigmoid fistula.…”
Section: Discussionmentioning
confidence: 59%
“…612 The presence of poly n-butylcyanoacrylate as a major component of urine bladder stone in our patient leads to an assumption that poly n-butylcyanoacrylate used in therapy of seroma was released into the bladder and thus became the crucial part of the concretion formation. The mechanism of the cyanoacrylate release into the bladder could be also explained by the mesh erosion caused by secondary migration as a result of erosion of the surrounding tissue, 1315 but this was not the case of our patient. Some recent studies demonstrated cyanoacrylate bladder stone formation following occlusion of vesicosigmoid fistula.…”
Section: Discussionmentioning
confidence: 59%
“…Potential complications related to urinary bladder mobilization include bladder injury, urinary retention, and hematoma. Regarding the mesh, Kok et al described a urinary bladder erosion, with fistulation to the abdominal wall resulting in necrotizing fasciitis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the data (10) every year more than 20 million patients undergo hernia repair. Just like any invasive intervention hernia repair is associated with several complications, such as migration of the mesh into the ab- dominal cavity (11,12), development of persistent seroma posterior (13)(14)(15), development of chronic pain (16,17), and surgical infection. Although incisional hernia repair is classified as a clean surgery, it still has a high incidence of surgical site infection (SSI) (0.7%-26.6%).…”
Section: Discussionmentioning
confidence: 99%